Advanced Modeling and Simulation of Rockfall Attenuator Barriers Via Partitioned DEM-FEM Coupling - Sautter, Klaus Bernd; Hofmann, Helene; Wendeler, Corinna; Wilson, Peter; Bucher, Philipp; Bletzinger, Kai-Uwe; Wüchner, Roland (Frontiers in Built Environment, 2021)
Attenuator barriers, in contrast to conventional safety nets, tend to smoothly guide impacting rocks instead of absorbing large amounts of strain energy arresting them. It has been shown that the rock's rotation plays an important role in the bearing capacity of these systems. Although experimental tests have to be conducted to gain a detailed insight into the behavior of both the structures and the rock itself, these tests are usually costly, time-consuming, and offer limited generalizability to other structure/environment combinations. Thus, in order to support the engineer's design decision, reinforce test results and confidently predict barrier performance beyond experimental configurations this work describes an appropriate numerical modeling and simulation method of this coupled problem. For this purpose, the Discrete Element Method (DEM) and the Finite Element Method (FEM) are coupled in an open-source multi-physics code. In order to flexibly model rocks of any shape, sphere clusters are used which employ simple and efficient contact algorithms despite arbitrarily complicated shapes. A general summary of the FEM formulation is presented as well as detailed derivations of finite elements particularly pertinent to rockfall simulations. The presented modeling and coupling method is validated against experimental testing conducted by the company Geobrugg. Good agreement is achieved between the simulated and experimental results, demonstrating the successful practical application of the proposed method.